Seasonal influenza vaccination coverage and its determinants among nursing homes personnel in western France - Christelle Elias; Anna Fournier; Anca Vasiliu; Nicolas Beix; Rémi Demillac; Hélène Tillaut; Yvonnick Guillois; Serge Eyebe; Bastien Mollo; Pascal Crépey (BMC, 2017)
Abstract Background Influenza-associated deaths is an important risk for the elderly in nursing homes (NHs) worldwide. Vaccination coverage among residents is high but poorly effective due to immunosenescence. Hence, vaccination of personnel is an efficient way to protect residents. Our objective was to quantify the seasonal influenza vaccination (IV) coverage among NH for elderly workers and identify its determinants in France. Methods We conducted a cross-sectional study in March 2016 in a randomized sample of NHs of the Ille-et-Vilaine department of Brittany, in western France. A standardized questionnaire was administered to a randomized sample of NH workers for face-to-face interviews. General data about the establishment was also collected. Results Among the 33 NHs surveyed, IV coverage for the 2015-2016 season among permanent workers was estimated at 20% (95% Confidence Interval (CI) 15.3%-26.4%) ranging from 0% to 69% depending on the establishments surveyed. Moreover, IV was associated with having previously experienced a "severe" influenza episode in the past (Prevalence Ratio 1.48, 95% CI 1.01-2.17), and varied by professional categories (p < 0.004) with better coverage among administrative staff. Better knowledge about influenza prevention tools was also correlated (p < 0.001) with a higher IV coverage. Individual perceptions of vaccination benefits had a significant influence on the IV coverage (p < 0.001). Although IV coverage did not reach a high rate, our study showed that personnel considered themselves sufficiently informed about IV. Conclusions IV coverage remains low in the NH worker population in Ille-et-Vilaine and also possibly in France. Strong variations of IV coverage among NHs suggest that management and working environment play an important role. To overcome vaccine "hesitancy", specific communication tools may be required to be adapted to the various NH professionals to improve influenza prevention.